The Influence of Audit Experience, Audit Digitalization, Audit Fees and Quality of Audit Results as Intervening Variables on Survey Audit Performance at Public Accounting Firms in Central Java - Kristianto, Djoko; Avianty, Hani Dyah (Journal of International Accounting, Taxation and Information Systems, 2025)
This study investigates the effects of audit experience, digitalization, audit fees, and audit quality on auditor performance, focusing on public accounting firms in Central Java. Using data from 49 respondents, the research emphasizes the role of financial reports as a communication tool between companies and stakeholders. Audit fees are influenced by assignment risks, service complexity, and the required expertise. Discrepancies in fee determination may indicate reduced auditor motivation. Auditor experience varies, impacting performance and professional conduct. More experienced auditors tend to demonstrate higher professionalism, which often correlates with higher fees and better audit quality. The findings reveal that audit experience, digitalization, and audit fees significantly affect auditor performance. Additionally, high-quality audit results also contribute positively to performance outcomes. Effective audits demand adequate resources, strong adherence to standards, and mastery of digital tools to ensure thorough and efficient processes. Ultimately, auditors who possess both technical expertise and ethical understanding are better equipped to deliver reliable audit services.